Investigation of the Heterovalent Substitution Cadmium for Lanthanum in Molybdate La2MoO6 - K. A. Chebyshev; A. V. Ignatov; L. V. Pasechnik; N. I. Selikova; E. I. Get`man (Journal of Chemistry)
This paper presents the investigation of the heterovalent substitution of cadmium for lanthanum in the La2-xCdxMoO6-x/2 system. The samples were synthesized by the solid state reaction method at 1000°C. The samples were characterized by X-ray powder diffraction with Rietveld refinements, scanning electron microscopy with energy-dispersive X-ray spectroscopy, and Fourier transform infrared spectroscopy methods. The study results revealed that cadmium incorporation in the lanthanum molybdate leads to the transformation of the tetragonal structure of La2MoO6 to a cubic fluorite-like one. The content of the cubic phase reaches 94% in the Lа1.4Cd0.6MoO5.7 sample. The unit cell parameter of fluorite-like-phase decreases with cadmium content rising. The preferred location of cadmium ions in the cubic structure was established by the Rietveld refinement method. The heterovalent substitution cadmium for lanthanide in tetragonal La2MoO6 molybdate leads to the cubic fluorite phase stabilization in a similar way as it occurs in the process of reduction.